Effects of diet on experimentally induced intestinal ulcers in rats: morphology and tissue leukotrienes. Issue 8 (August 1994) - Matsumoto, T; Iida, M; Kuroki, F; Hizawa, K; Koga, H; Fujishima, M
Abstract : The effects of dietary pretreatment on longitudinal ulcers of the intestine induced by indomethacin given intracolonically were investigated in rats. The rats were pretreated with either standard diet or liquid meals. Intracolonic indomethacin (24 mg/kg/day) given for two days produced longitudinal ulcers and small scattered ulcers in the small intestine in the control rats that were receiving standard pelleted formula. Three days pretreatment with one of two types of liquid meals, low residual diet (LRD) or elemental diet (ED), significantly reduced the incidence (3% in ED group and 0% in the LRD group) and the length of the longitudinal ulcers in the small intestine. The caecum was affected in each dietary pretreatment group (67% in controls, 80% in LRD group, and 69% in ED group). Colonic ulcers that were located in a longitudinal fashion were found in 42% of LRD group, while these ulcers were less frequently found in the ED group (13%) and controls (0%). Development of ulcers in the caecum and in the colon of rats in ED and LRD groups was more delayed than that of small intestinal ulcers of control rats. In another experiment, pretreatment by ED significantly increased colonic tissue leukotriene B4 concentration when compared with that of controls. These findings suggest that the site of experimental enteropathy induced by indomethacin given intracolonically can be modified by dietary pretreatment. This animal model can be available for investigating differences in the pathophysiology of enteropathy according to the site of involvement.